2020
DOI: 10.1523/jneurosci.2947-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Neurons of the Ventral Tegmental Area Encode Individual Differences in Motivational “Wanting” for Reward Cues

Abstract: It has been argued that the dopaminergic system is involved in the attribution of motivational value to reward predictive cues as well as prediction error. To evaluate, dopamine neurons were recorded from male rats performing a Pavlovian approach task containing cues that have both "predictive" and "incentive" properties. All animals learned the predictive nature of the cue (illuminated lever entry into cage), but some also found the cue to be attractive and were motivated toward it ("sign-trackers," STs). "Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 46 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…For example, humans with genetic polymorphisms that result in elevated DA system activity show greater reward cue-evoked striatal activity and craving that could denote a predisposition toward exaggerated drug use (Wittmann et al, 2013;Ray et al, 2014). Consistent with this, in animal models, variability in DA signaling and expression of striatal DA receptors is associated with higher drug cue responsivity and relapse (Flagel et al, 2007;Verheij and Cools, 2008;Piray et al, 2010;Saunders et al, 2013;Klanker et al, 2015;Ferguson et al, 2020). Furthermore, at certain stages of the estrus cycle, female rodents have larger NAc DA signals in response to cocaine and cocaine-associated cues, which is thought to underlie their generally higher propensity for addiction-like behaviors (Becker and Cha, 1989;Becker, 1999;Calipari et al, 2017;Johnson et al, 2019).…”
Section: Individual Differences In Substance Use Disorder Vulnerabilitymentioning
confidence: 81%
“…For example, humans with genetic polymorphisms that result in elevated DA system activity show greater reward cue-evoked striatal activity and craving that could denote a predisposition toward exaggerated drug use (Wittmann et al, 2013;Ray et al, 2014). Consistent with this, in animal models, variability in DA signaling and expression of striatal DA receptors is associated with higher drug cue responsivity and relapse (Flagel et al, 2007;Verheij and Cools, 2008;Piray et al, 2010;Saunders et al, 2013;Klanker et al, 2015;Ferguson et al, 2020). Furthermore, at certain stages of the estrus cycle, female rodents have larger NAc DA signals in response to cocaine and cocaine-associated cues, which is thought to underlie their generally higher propensity for addiction-like behaviors (Becker and Cha, 1989;Becker, 1999;Calipari et al, 2017;Johnson et al, 2019).…”
Section: Individual Differences In Substance Use Disorder Vulnerabilitymentioning
confidence: 81%
“…In addition, we showed that brief optical activation of D2-MSNs paired with a reward-predicting cue enhances motivation to obtain food rewards ( Soares-Cunha et al., 2016b , 2018 ). Part of this behavioral effect was triggered by a transient decrease in the activity of VP GABAergic neurons that resulted in the disinhibition of VTA dopaminergic activity ( Soares-Cunha et al., 2018 , 2020 ), which is known to increase motivational levels ( Ferguson et al., 2020 ; Ilango et al., 2014 ; Mohebi et al., 2019 ). However, others showed that chemogenetic inhibition of D2-MSNs during a progressive ratio task enhances motivation, without affecting sensitivity for reward devaluation ( Carvalho Poyraz et al., 2016 ), and causes animals to initiate more frequently behavior without goal-directed efficiency ( Gallo et al., 2018 ), an effect caused by disinhibition of VP GABAergic activity ( Gallo et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The seeking system consists mainly of dopaminergic neurons in the ventral tegmental area (VTA) of the midbrain [ 23 ] and its projections to the nucleus accumbens (NAc) in the ventral striatum and prefrontal (PFC) and frontal (FC) cortices ( Figure 3 A). Following exposure to relevant stimuli dopamine (DA) is released to the synaptic cleft where it binds DA receptors [ 24 , 25 , 26 ]. One study in primates showed that DA release occurred following unexpected rewards (food), but also following exposure to conditioned stimulus (a light) and anticipated reward (food).…”
Section: The Seven Basic Neurobiological Systems Of Behaviormentioning
confidence: 99%